A global risk approach to assessing groundwater vulnerability. (February 2017) - Allouche, Nabila; Maanan, Mohamed; Gontara, Mona; Rollo, Nicolas; Jmal, Ikram; Bouri, Salem
Abstract: This research provides a new approach to assess groundwater vulnerability to contamination from anthropogenic activities and sea water intrusion. The DRASTIC and GALDIT parametric methods were then linked to a novel land use index to create a more robust "global risk index", useful for assessing aquifer vulnerability to pollution and seawater intrusion risk. In addition, sensitivity analysis was used to evaluate the effect of each individual parameter on the final models. The vulnerability to pollution and the seawater intrusion contamination maps show three classes of water resources degradation: low, moderate and high, relating to the intrinsic properties. In addition, the global risk map shows three risk classes': low (25%), moderate (64%) and high (11%) depending on the hydrogeological characteristics, land use, distance from the coast and human impacts in most of the study area. The modified models were statistically compared with the nitrate concentration and the water resistivity values for validation. These maps are considered indispensable for sustainable land use planning and groundwater management of the shallow aquifer. Highlights: Land use is one of the factors controlling the vulnerability of groundwater pollution. Combining models with GIS offers an effective approach for environmental modeling. The global index provides a powerful tool to asses' groundwater pollution risk. Groundwater vulnerability maps are clearly useful in land use planning. The results provide scientifically defensible information for decision makers.